TRPC6 counteracts TRPC3-Nox2 protein complex leading to attenuation of hyperglycemia-induced heart failure in mice - Oda, Sayaka (Sci Rep, 2017)
Excess production of reactive oxygen species (ROS) caused by hyperglycemia is a major risk factor for heart failure. We previously reported that transient receptor potential canonical 3 (TRPC3) channel mediates pressure overload-induced maladaptive cardiac fibrosis by forming stably functional complex with NADPH oxidase 2 (Nox2). Although TRPC3 has been long suggested to form hetero-multimer channels with TRPC6 and function as diacylglycerol-activated cation channels coordinately, the role of TRPC6 in heart is still obscure. We here demonstrated that deletion of TRPC6 had no impact on pressure overload-induced heart failure despite inhibiting interstitial fibrosis in mice. TRPC6-deficient mouse hearts 1 week after transverse aortic constriction showed comparable increases in fibrotic gene expressions and ROS production but promoted inductions of inflammatory cytokines, compared to wild type hearts. Treatment of TRPC6-deficient mice with streptozotocin caused severe reduction of cardiac contractility with enhancing urinary and cardiac lipid peroxide levels, compared to wild type and TRPC3-deficient mice. Knockdown of TRPC6, but not TRPC3, enhanced basal expression levels of cytokines in rat cardiomyocytes. TRPC6 could interact with Nox2, but the abundance of TRPC6 was inversely correlated with that of Nox2. These results strongly suggest that Nox2 destabilization through disrupting TRPC3-Nox2 complex underlies attenuation of hyperglycemia-induced heart failure by TRPC6.